Characterisations and DSSC efficiency test of TiO2nano-films formed by filtered cathodic vacuum arc deposition - C. Aramwit (2018)
Copyright © 2017 Inderscience Enterprises Ltd. For photovoltaic applications in dye-sensitised solar cells (DSSC), used as a wide band semiconductor layer, titanium dioxide (TiO2) nano-films were formed by the filtered cathodic vacuum arc deposition (FCVAD) technique using Ti as the cathode and controlled oxygen (O2) gas inlet under varied deposition and post-deposition annealing conditions. The deposition conditions included the O2pressure as the key parameter and others such as deposition time and bias. The work was aimed at investigating the FCVAD condition effect on the TiO2film characteristics and thus the solar cell efficiency. The formed films were characterised using optical microscopy, scanning electron microscopy (SEM), atomic force microscopy (AFM), energy-dispersive X-ray spectroscopy (EDS), Raman spectroscopy and scanning photoemission microscopy (SPEM) techniques. All the characterisations revealed that the film transparency increased and thickness decreased to a nanoscale with increasing of the O2pressure, the transparent deposited films contained stoichiometric titanium and oxygen under the medium O2pressure, the as-deposited films were TiO2containing some rutile but without anatase, and the annealing improved the film quality by introducing anatase and increasing the Ti-oxide. Test of the films for the DSSC-photovoltaic property efficiency showed that the efficiency of using the annealed films was 104times that of using the as-deposited films, indicating the crucial significance of the anatase.